## Chapter - 6, Mathematical Induction

### Section - 6.1 - Proof by Mathematical Induction

### Summary

- To prove a goal of the form $\forall n \in N P(n)$:

First prove $P(0)$, and then prove $\forall n \in N(P(n) \to P(n + 1))$. The first of these proofs is sometimes called the base case and the second the induction step. - Form of the final proof:

Base case: [Proof of $P(0)$ goes here.] Induction step: [Proof of $\forall n \in N(P(n) \to P(n + 1))$ goes here.].

**Soln1**

By Mathematical induction:

__Base Case:__

For $n = 0$, $0 = \frac {0(0 + 1)} 2 = 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $0 + 1 + 2 + \cdot \cdot \cdot + n = \frac {n(n+1)} 2$.

Thus we have $0 + 1 + 2 + \cdot \cdot \cdot + n + (n + 1) = (\frac {n(n+1)} 2) + (n+1)$.

$\quad = \frac {n(n+1) + 2(n+1)} 2$.

$\quad = \frac {(n+1)(n + 2)} 2$.

$\quad = \frac {(n+1)(n + 1 + 1)} 2$.

Thus if $P(n)$ is true then $P(n+1)$ is also true.

**Soln2**

By Mathematical induction:

__Base Case:__

For $n = 0$, $0^2 = \frac {0(0 + 1)(2 \times 0 + 1)} 6 = 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $0^2 + 1^2 + 2^2 + \cdot \cdot \cdot + n^2 = \frac {n(n+1)(2n+1)} 6$.

Thus we have $0^2 + 1^2 + 2^2 + \cdot \cdot \cdot + n^2 + (n+1)^2 = {\frac {n(n+1)(2n+1)} 6} + (n+1)^2$.

$= \frac {n(n+1)(2n+1) + 6(n+1)^2} 6$.

$= \frac {(n+1)(n(2n+1) + 6(n+1))} 6$.

$= \frac {(n+1)(2n^2 + 7n + 6)} 6$.

$= \frac {(n+1)(n+2)(2n+3)} 6$.

$= \frac {(n+1)(n+1+1)(2(n+1)+1)} 6$.

Thus $P(n+1)$ is also true if $P(n)$ is true.

**Soln3**

By Mathematical induction:

__Base Case:__

For $n = 0$, $0^3 = {(\frac {0(0 + 1)} 2 = 0)}^2 = 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $0^3 + 1^3 + 2^3 + \cdot \cdot \cdot + n^3 = {(\frac {n(n+1)} 2)}^2$.

Thus we have $0^3 + 1^3 + 2^3 + \cdot \cdot \cdot + n^3 + (n+1)^3 = {(\frac {n(n+1)} 2)}^2 + (n+1)^3$.

$= (\frac {n^2 \times (n+1)^2 } 4) + (n+1)^3$.

$= \frac {n^2 (n+1)^2 + 4{(n+1)}^3} 4$.

$= \frac {(n+1)^2(n^2 + 4(n+1))} 4$.

$= \frac {(n+1)^2(n^2 + 4n + 4)} 4$.

$= \frac {(n+1)^2(n+2)^2} 4$.

$= {(\frac {(n+1)(n+1+1)} 2)}^2$.

Thus $P(n+1)$ is also true if $P(n)$ is true.

**Soln4**

To find the formulae we may proceed as:

In the given series it includes only odd numbers. Consider the series containing both odd and even terms:

$0,1,2,3, \cdot \cdot \cdot (2n-1), (2n)$. Thus we have total $2n$ terms. We know from soln1 sum of this = $2n(2n+1)/2$.

Clearly if we remove all the even terms from this we will get our series. Also we have $n$ even terms and $n$ odd terms. Since we will always have atleast one term( becuase $n>=1$), we can think of the above modified series as consisting of pairs where each pair is one odd number and one even number with even number = 1 + odd number. Thus we have $n$ such pairs. Suppose sum of odd terms is $x$. Then clearly since each pair consists of one odd and one even term with even term = 1 + odd term. Thus sum of even terms is sum of odd terms and total number of pairs. Thus sum of even terms = $x + n$. Total sum is sum of all even and all odd terms. Thus we have $x + (x+n) = 2n(2n+1)/2$. On symplifying it gives $x = n^2$.

Thus sum of the required/given series = $n^2$.

We shall prove by inductions that $n^2$ is correct sum.

__Base Case:__

For $n = 1$, $1 = 1^2 = 1$. Thus $P(1)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $1 + 3 + 5 + \cdot \cdot \cdot + (2n-1) = n^2$.

Thus we have $1 + 3 + 5 + \cdot \cdot \cdot + (2n-1) + (2(n+1)-1) = n^2 + (2(n+1)-1)$.

$= n^2 + 2n + 1 = (n+1)^2$.

Thus $P(n+1)$ is also true if $P(n)$ is true.

**Soln5**

By Mathematical induction:

__Base Case:__

For $n = 0$, $0 \cdot 1 = 0(0+1)(0+2)/3 = 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $0 \cdot 1 + 1 \cdot 2 + 2 \cdot 3 + \cdot \cdot \cdot + n(n+1) = n(n+1)(n+2)/3$.

Thus we have $0 \cdot 1 + 1 \cdot 2 + 2 \cdot 3 + \cdot \cdot \cdot + n(n+1) + (n+1)(n+1+1)$.

$= n(n+1)(n+2)/3 + (n+1)(n+1+1)$.

$= n(n+1)(n+2)/3 + (n+1)(n+2)$.

$= (n(n+1)(n+2) + 3(n+1)(n+2))/3$.

$= (n+1)(n+2)(n + 3)/3$.

$= (n+1)(n+1+1)(n + 1 + 2)/3$.

Thus $P(n+1)$ is also true if $P(n)$ is true.

**Soln6**

By looking at Ex1 and Ex5, it seems that formulae is $n(n+1)(n+2)(n+3)/4$.

We shall prove that formulae is correct by Mathematical induction:

__Base Case:__

For $n = 0$, $0 \cdot 1 \cdot 2 = 0(0+1)(0+2)(0+3)/4 = 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $0 \cdot 1 \cdot 2 + 1 \cdot 2 \cdot 3 + 2 \cdot 3 \cdot 4 + \cdot \cdot \cdot + n(n+1)(n+2) = n(n+1)(n+2)(n+3)/4$.

Thus we have $0 \cdot 1 \cdot 2 + 1 \cdot 2 \cdot 3 + 2 \cdot 3 \cdot 4 + \cdot \cdot \cdot + n(n+1)(n+2) + (n+1)(n+1+1)(n+1+2)$.

$= n(n+1)(n+2)(n+3)/4 + (n+1)(n+1+1)(n+1+2)$.

$= n(n+1)(n+2)(n+3)/4 + (n+1)(n+2)(n+3)$.

$= (n(n+1)(n+2)(n+3) + 4(n+1)(n+2)(n+3))/4$.

$= (n+1)(n+2)(n+3)(n+4)/4$.

$= (n+1)(n+1+1)(n+1+2)(n+1+3)/4$.

Thus $P(n+1)$ is also true if $P(n)$ is true.

**Soln7**

By checking the example mentioned and with some hit and try, it seems that formulae is $(3^{n+1} -1)/2$.

__Base Case:__

For $n = 0$, $3^0 = (3^{0+1} -1)/2 = 1$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $3^0 + 3^1 + 3^2 + 3^3 + \cdot \cdot \cdot + 3^n = (3^{n+1} -1)/2$.

Thus we have $3^0 + 3^1 + 3^2 + 3^3 + \cdot \cdot \cdot + 3^n + 3^{n+1}$.

$= (3^{n+1} -1)/2 + 3^{n+1}$.

$= ((3^{n+1} -1) + (2 \cdot 3^{n+1}))/2$.

$= (3 \cdot 3^{n+1} - 1)/2$.

$= (3^{n+1+1} - 1)/2$.

Thus $P(n+1)$ is also true if $P(n)$ is true.

**Soln8**

First we can observe that on LHS there are $2n$ terms and on RHS there are $n$ terms.

By Mathematical induction:

__Base Case:__

For $n = 1$. LHS will contain two terms = $\frac 1 {2 \cdot 1 - 1} - \frac 1 {2 \cdot 1} = 1 - \frac 1 2$. And RHS will contain one term = $\frac 1 {1+1} = \frac 1 2$. Thus $LHS = RHS$, $P(1)$ is true.

__Induction Step:__

Suppose $P(n)$ is true.

Thus $1 - \frac 1 2 + \frac 1 3 - \frac 1 4 + \cdot \cdot \cdot + \frac 1 {2n-1} - \frac 1 {2n} = \frac 1 {n+1} + \frac 1 {n+2} + \frac 1 {n+3} + \cdot \cdot \cdot + \frac 1 {2n}$.

Thus LHS for $P(n+1)$ is:

$1 - \frac 1 2 + \frac 1 3 - \frac 1 4 + \cdot \cdot \cdot + \frac 1 {2(n+1)-3} - \frac 1 {2(n+1) - 2} + \frac 1 {2(n+1)-1} - \frac 1 {2(n+1)}$.

$= 1 - \frac 1 2 + \frac 1 3 - \frac 1 4 + \cdot \cdot \cdot + \frac 1 {2n-1} - \frac 1 {2n} + \frac 1 {2(n+1)-1} - \frac 1 {2(n+1)}$.

Clearly except last two terms, it is equivalent to LHS of $P(n)$. Thus we can replace this with RHS of $P(n)$ as $P(n)$ is true. Thus we have:

$\frac 1 {n+1} + \frac 1 {n+2} + \frac 1 {n+3} + \frac 1 {n+4} + \cdot \cdot \cdot + \frac 1 {2n} + \frac 1 {2(n+1)-1} - \frac 1 {2(n+1)}$.

Moving first term to the end:

$= \frac 1 {n+2} + \frac 1 {n+3} + \frac 1 {n+4} + \cdot \cdot \cdot + \frac 1 {2n} + \frac 1 {2(n+1)-1} - \frac 1 {2(n+1)} + \frac 1 {n+1}$.

On adding last two terms:

$= \frac 1 {n+2} + \frac 1 {n+3} + \frac 1 {n+4} + \cdot \cdot \cdot + \frac 1 {2n} + \frac 1 {2(n+1)-1} + \frac 1 {2(n+1)}$.

$= \frac 1 {n+1+1} + \frac 1 {n+1+2} + \frac 1 {n+1+3} + \cdot \cdot \cdot + \frac 1 {2n} + \frac 1 {2(n+1)-1} + \frac 1 {2(n+1)}$.

Clearly it is equivalent to RHS of $P(n+1)$. Thus LHS and RHS of $P(n+1)$ are equal. Or $P(n+1)$ is true.

Thus if $P(n)$ is true then $P(n+1)$ is also true.

**Soln9**

**(a)**

By Mathematical induction:

__Base Case:__

For $n = 0$. We have $0^2 + 0 = 0 = 2 \times 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus for some integer $k$, $2k = n^2 + n$.

Thus we have for $P(n+1)$: $(n+1)^2 + n+1 = n^2 + 2n + 1 + n + 1 = n^2 + n + 2n + 2$.

Since $n^2 + 2n = 2k$, we get $(n+1)^2 + n+1 = 2k + 2n + 2 = 2(k+n+1)$. Clearly for $l = k + n + 1$, $(n+1)^2 + n+1$ is divisible by $2$. Thus if $P(n)$ is correct then $P(n+1)$ is also correct.

**(b)**

By Mathematical induction:

__Base Case:__

For $n = 0$. We have $0^3 - 0 = 0 = 6 \times 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus for some integer $k$, $6k = n^3 - n$.

Thus we have for $P(n+1)$: $(n+1)^3 - (n+1) = n^3 + 1 + 3n^2 + 3n - n - 1 = n^3 - n + 3n^2 + 3n = 6k + 3(n^2 + n)$.

Since from part(a) $n^2 + n$ is divisible by $2$, it follows $n^2 + n = 2l$ where $l$ is integer. Thus we have:

$(n+1)^3 - (n+1) = 6k + 3(2l) = 6k + 6l = 6(k+l)$. Clearly $k+l$ is integer, thus $P(n+1)$ is also true.

**Soln10**

By Mathematical induction:

__Base Case:__

For $n = 0$, we have $9^0 - 8 \times 0 - 1 = 0 = 64 \times 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus for some integer $k$, $64k = 9^n - 8n - 1$. Thus $9^n = 64k + 8n + 1$. Thus for $P(n+1)$ we have:

$9^{n+1} -8(n+1) -1$.

$= 9^{n+1} -8n - 9$.

$= 9 \cdot 9^n -8n - 9$.

$= 9 \cdot (64k + 8n + 1) -8n - 9$.

$= 9 \times 64k + 9 \times 8n + 9 -8n - 9$.

$= 9 \times 64k + 64n$.

$= 64(9k + n)$.

$= 64m$, where $m = 9k+n$ is an integer.

Thus $P(n+1)$ is true.

**Soln11**

By Mathematical induction:

__Base Case:__

For $n = 0$, we have $4^0 + 6 \times 0 - 1 = 0 = 9 \times 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus for some integer $k$, $9k = 4^n + 6n - 1$. Thus $4^n = 9k - 6n + 1$. Thus for $P(n+1)$ we have:

$4^{n+1} + 6(n+1) -1$.

$= 4 \cdot 4^n + 6n + 5$.

$= 4 \cdot (9k - 6n + 1) + 6n + 5$.

$= 4 \times 9k - 4 \times 6n + 4 + 6n + 5$.

$= 4 \times 9k - 3 \times 6n + 9$.

$= 9 (4k - 2n + 1)$.

$= 9m$, where $m = 4k - 2n + 1$ is an integer.

Thus $P(n+1)$ is true.

**Soln12**

By Mathematical induction:

__Base Case:__

For $n = 0$, we have $a^0 - b^0 = 0 = (a-b) \times 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus for some integer $k$, $(a-b)k = a^n - b^n$.

Thus for $P(n+1)$ we have:

$a^{n+1} - b^{n+1}$.

$= a(a^n - b^n) - b^{n+1} + ab^n$.

$= a(a-b)k + b^n(a-b)$.

$= (a-b)(ak + b^n)$.

$= (a-b)m$, where $m = ak + b^n$ is an integer.

Thus $P(n+1)$ is true.

**Soln13**

By Mathematical induction:

__Base Case:__

For $n = 0$, we have $a^{2 \times 0 + 1} + b^{2 \times 0 + 1} = a+b = (a+b) \times 1$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus for some integer $k$, $(a+b)k = a^{2n + 1} + b^{2n + 1}$.

Thus for $P(n+1)$ we have:

$a^{2(n+1)+1} + b^{2(n+1)+1}$.

$= a^{2n+3} + b^{2n+3}$.

$= a^2(a^{2n+1} + b^{2n+1}) + b^{2n+3} - a^2 \cdot b^{2n+1}$.

$= a^2(a+b)k + b^{2n+1}(b^2 - a^2)$.

$= a^2(a+b)k + b^{2n+1}(b - a)(b+a)$.

$= (a+b)(a^2k + b^{2n+1}(b - a))$.

$= (a+b)m$, where $m = a^2k + b^{2n+1}(b - a)$ is an integer.

Thus $P(n+1)$ is true.

**Soln14**

By Mathematical induction:

__Base Case:__

For $n = 10$, we have $2^10 = 1024 > 10^3 = 1000$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $2^n > n^3$.

Thus for $P(n+1)$ we have $2^{n+1}$:

$= 2 \cdot 2^n$.

$> 2 \cdot n^3$, since $2^n > n^3$.

$= n^3 + n^3$.

$\ge n^3 + 10n^2$, since $n \ge 10$.

$= n^3 + 3n^2 + 7n^2$.

$\ge n^3 + 3n^2 + 70n$, since $n \ge 10$.

$= n^3 + 3n^2 + 3n + 67n$.

$> n^3 + 3n^2 + 3n + 1$, since $n \ge 10$ means $67n \ge 1$.

$= (n+1)^3$.

Thus $P(n+1)$ is true.

**Soln15**

By Mathematical induction:

__Base Case:__

For $n = 0$, we have $(n-0) = 0 = 3 \times 0$. Thus $n \equiv 0 (mod 3)$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus atleast one of the following is true:

- $n = 3k$.
- $n - 1 = 3l$.
- $n - 2 = 3m$.

where $k,l,m$ are integers.

Now consider $P(n + 1)$, we have following possible cases:

Case 1: $n = 3k$.

Thus $n + 1 = 3k+1$, or $(n+1) - 1 = 3k$. Thus $(n+1) \equiv 1 (mod 3)$.

Case 2: $n - 1 = 3l$.

Thus $n + 1 = 3l+1+1$, or $(n+1) - 2 = 3l$. Thus $(n+1) \equiv 2 (mod 3)$.

Case 3: $n - 2 = 3m$.

Thus $n + 1 = 3(m+1)$, or $(n+1) - 0 = 3m$. Thus $(n+1) \equiv 0 (mod 3)$.

Thus from all cases, $P(n+1)$ is also true.

**Soln16**

By Mathematical induction:

__Base Case:__

For $n = 1$, we have $(1+1)2^1 = 4 = 1 \times 2^{1+1}$. Thus $P(1)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $2 \cdot 2^1 + 2 \cdot 2^1 + 2 \cdot 2^1 + \cdot \cdot \cdot + (n+1) \cdot 2^n = n \cdot 2^{n+1}$.

Thus for $P(n+1)$ we have $2 \cdot 2^1 + 2 \cdot 2^1 + 2 \cdot 2^1 + \cdot \cdot \cdot + (n+1) \cdot 2^n + (n+2) \cdot 2^{n+1}$.

$= n \cdot 2^{n+1} + (n+2) \cdot 2^{n+1}$, since $P(n)$ is true.

$= 2^{n+1}(n+n+2)$.

$= 2^{n+1} \cdot 2(n+1)$.

$= (n+1) \cdot 2^{n+1+1}$.

Thus $P(n+1)$ is also true.

**Soln17**

**(a)** Base case is not covered.

**(b)** It appears formulae should be $n \cdot 3^{n+1} + 1$.

By Mathematical induction:

__Base Case:__

For $n = 0$, we have $(2 \times 0 + 1) \cdot 3^0 = 1 = 0 \cdot 3^{0+1} + 1$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $1 \cdot 3^0 + 3 \cdot 3^1 + 5 \cdot 3^2 + \cdot \cdot \cdot + (2n + 1) \cdot 3^n = n \cdot 3^{n+1} + 1$.

Thus for $P(n+1)$ we have $1 \cdot 3^0 + 3 \cdot 3^1 + 5 \cdot 3^2 + \cdot \cdot \cdot + (2n + 1) \cdot 3^n + (2(n+1) + 1) \cdot 3^{n+1}$.
$= n \cdot 3^{n+1} + 1 + (2(n+1) + 1) \cdot 3^{n+1}$, since $P(n)$ is true.

$= n \cdot 3^{n+1} + (2n + 3) \cdot 3^{n+1} + 1$.

$= 3^{n+1}(n + (2n + 3)) + 1$.

$= 3^{n+1}(3n+3) + 1$.

$= (n+1) \cdot 3^{n+1+1} + 1$.

Thus $P(n+1)$ is true.

**Soln18**

By Mathematical induction:

__Base Case:__

For $n = 0$. Thus $n$ is odd. So we have $a^0 = 1 > 0$. Thus $P(0)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus if $n$ is odd, $a^n < 0$ and if $n$ is even $a^n > 0$.

Thus for $P(n+1)$ we have following cases:

Case 1: $n$ is odd.
Thus $a^{n+1} = a \cdot a^n$. Also since $P(n)$ is true and $n$ is odd, $a^n < 0$. Since $a < 0$ and

$a^n < 0$, it follows that $a \cdot a^n > 0$. Thus $a^{n+1} > 0$. Since $n$ is odd, it follows $n+1$ is
even. Thus $P(n+1)$ is true if $n$ is odd.

Case 2: $n$ is even.
Thus $a^{n+1} = a \cdot a^n$. Also since $P(n)$ is true and $n$ is even, $a^n > 0$. Since $a < 0$ and

$a^n > 0$, it follows that $a \cdot a^n < 0$. Thus $a^{n+1} < 0$. Since $n$ is even, it follows $n+1$ is
odd. Thus $P(n+1)$ is true if $n$ is even.

Thus $P(n+1)$ is true for all possible cases.

**Soln19**

Suppose $0 < a < b$.

**(a)**

By Mathematical induction:

__Base Case:__

For $n = 1$. Thus $a^1 = a$ and $b^1 = b$. Clearly from the give $a < b$. Thus $P(1)$ is true.

__Induction Step:__

Suppose $P(n)$ is true. Thus $0 < a^n < b^n$.

Thus for $P(n+1)$ we have $b^{n+1}$:
$= b \cdot b^n$.

$> a \cdot b^n$, Since $b > a$.

$> a \cdot a^n$, Since $b^n > a^n$.

$= a^{n+1}$.

Since $P(n)$ is true, $a^n > 0$. Since $a > 0$, it follows $a \cdot a^{n+1} > 0$. Thus $a^{n+1} > 0$.

Thus $0 < a^{n+1} < b^{n+1}$. It follows $P(n+1)$ is true.

**(b)**

By definition of $\sqrt[n] a$, we have $\sqrt[n] a > 0$. Thus we only need to prove $\sqrt[n] a < \sqrt[n] b$.

Suppose $p = \sqrt[n] a$ and $q = \sqrt[n] b$. We will prove this by contradiction. Suppose $p > q$. Thus by part(a) we have $p^n > q^n$. It follows $(\sqrt[n] a)^n > (\sqrt[n] b)^n$. Thus $a > b$. But it contradicts with the given that $a < b$. Thus $\sqrt[n] a < \sqrt[n] b$.

**(c)**

To Prove $ab^n + ba^n < a^{n+1} + b^{n+1}$, which is equivalent to proving:

$\Leftrightarrow ab^n + ba^n - a^{n+1} - b^{n+1} < 0$.

$\Leftrightarrow b^n(a-b) - a^n(a-b)< 0$.

$\Leftrightarrow (a-b)(b^n - a^n)< 0$.

Since $0 < a < b$, $a - b < 0$. Also from part(a) $a^n < b^n$, or $b^n - a^n > 0$. Since $a-b > 0$ and $b^n - a^n > 0$, it follows $(a-b)(b^n - a^n)< 0$. Thus $ab^n + ba^n < a^{n+1} + b^{n+1}$ is true.

**(d)**

By Mathematical induction:

__Base Case:__

For $n = 2$. Thus we have to prove $(\frac {a+b} 2)^2 < \frac {a^2 + b^2} 2$, or $(a+b)^2 < 2(a^2 + b^2)$, which on simplifying $a^2 + b^2 + 2ab < 2a^2 + 2b^2$, or $2ab < a^2 + b^2$. Thus we need to prove $2ab < a^2 + b^2$. This is true as from part(c) for $n = 2$.

__Induction Step:__

Suppose $P(n)$ is true. Thus $(\frac {a+b} 2)^n < \frac {a^n + b^n} 2$.

Multiplying both sides by $(a+b)/2$, we get:

$(\frac {a+b} 2)^{n+1} < {\frac {a^n + b^n} 2} \times {\frac {a+b} 2}$.

$\Rightarrow (\frac {a+b} 2)^{n+1} < {\frac {a(a^n + b^n) + b(a^n + b^n)} 4}$.

$\Rightarrow (\frac {a+b} 2)^{n+1} < {\frac {a^{n+1} + ab^n + ba^n + b^{n+1}} 4}$.

Using part(c), $ab^n + ba^n < a^{n+1} + b^{n+1}$, we get:

$\Rightarrow (\frac {a+b} 2)^{n+1} < {\frac {a^{n+1} + a^{n+1} + b^{n+1} + b^{n+1}} 4}$.

$\Rightarrow (\frac {a+b} 2)^{n+1} < {\frac {a^{n+1+1} + b^{n+1+1}} 4}$.

Since $x > 0 \to \frac x 4 < \frac x 2$, we get:

$\Rightarrow (\frac {a+b} 2)^{n+1} < {\frac {a^{n+1+1} + b^{n+1+1}} 2}$.

Thus $P(n+1)$ is true.